2013
DOI: 10.1186/1471-2431-13-116
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the feasibility and coverage of a modified universal hearing screening protocol for use with newborn babies of migrant workers in Beijing

Abstract: BackgroundAlthough migrant workers account for the majority of newborns in Beijing, their children are less likely to undergo appropriate universal newborn hearing screening/rescreening (UNHS) than newborns of local non-migrant residents. We hypothesised that this was at least in part due to the inadequacy of the UNHS protocol currently employed for newborn babies, and therefore aimed to modify the protocol to specifically reflect the needs of the migrant population.MethodsA total of 10,983 healthy babies born… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Factors for Loss to follow-up Educational disparities and lack of knowledge among parents [24,25,28,34,35,52,65,67,74] Distance [26,30,33,48,52,54,62] Work constraints [24,26,33,35,54] Unfavorable attitudes [25,49,62,67,73] Less priority given to hearing compared to other medical conditions by parents [40,62,71,73] Rescreened at some other center [34,40,48] Inaccurate contact details [35,54,72] Change of Address [33,54,68] Superstitious and cultural beliefs [24,49,54] Barriers to adequate healthcare [65,71,74] Financial constraints [28,52,…”
Section: Sr Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Factors for Loss to follow-up Educational disparities and lack of knowledge among parents [24,25,28,34,35,52,65,67,74] Distance [26,30,33,48,52,54,62] Work constraints [24,26,33,35,54] Unfavorable attitudes [25,49,62,67,73] Less priority given to hearing compared to other medical conditions by parents [40,62,71,73] Rescreened at some other center [34,40,48] Inaccurate contact details [35,54,72] Change of Address [33,54,68] Superstitious and cultural beliefs [24,49,54] Barriers to adequate healthcare [65,71,74] Financial constraints [28,52,…”
Section: Sr Nomentioning
confidence: 99%
“…Measures to increase follow-up Database management system [28,38,60,63,64] Increased parental education [25,26,40,54] Telephone reminders [24,35,46,60] Multidisciplinary team [33,50,71] Flexibility in scheduling appointments [26,48] Visual reminders and written reports [60,71] Financial support [63,64] Handouts to parents [24,71] Psychological support [50,63] Counselling [25,46] Centralized screening facility [58] Scheduling at the time of immunization [47] Minimizing repeat visits [54] Verbal reminders [23] Text message/letters/reminders (single or in combination) [73] Reminders by community health care workers through home visits [60] Knowledge of local language and culture by screening personnel [60] Collaboration of state programs [68] Increasing knowledge of medical staff [40] Hearing screening reports sent to primary care physicians [71] Free screening and follow-up testing [33] Increasing knowledge of prospective mothers that hearing screening is of no harm [33] Scheduling follow-up testing at one week rather than six weeks…”
Section: Sr Nomentioning
confidence: 99%
“…as well as other recent publications. [ 9 14 15 16 17 ] While our newborn pass rate of 56.7% reflects a lower than average pass rate, there are numerous factors that explain this. First, 63.3% of the newborn infants screened in this study were <24 h old, which is shown to be associated with a lower pass rate.…”
Section: Discussionmentioning
confidence: 96%
“…Some of these studies have focused on coverage rates, referral rates and tracking systems associated with UNHS (Ng, Hui, Lam, Goh & Yeung, 2004 ; Pisacane et al ., 2013 ). Other studies have focused on the feasibility in terms of the type of screening protocol employed (Kumar et al ., 2014 ; Qi et al ., 2013 ). Feasibility studies are commonly performed in many clinical areas.…”
Section: Introductionmentioning
confidence: 99%